1st European Prize for Contemporary Art- and Design-Led Crafts 1998. - Wickman, Kerstin (Frankfurt ; Bruxelles : World Crafts Council Europe : European Association of Crafts, Small and Medium-Sized Enterprises, 1998)
Behn, Dörte ; Rowe, Michael ; Bartron, Paula ; Huycke, David ; Swärd, Ulrika ; Farthofer, Anton ; Bonde-Jensen, Kaarin ; Bontridder, Thierry ; Carter, Penny ; Chang, Peter ; Corregan, Daphne ; Densham, Karen ; Dessauvage, Tjok ; Dvorak, Petr ; Fernandez, Francisco-Javier ; Hoffmann, Berthold ; Houman, Charlotte ; Hurlin, Jean-Louis ; Jonemann, Gilles ; Kuku, Ola-Dele ; Leuner, Christoph ; Lindblad, Gun ; Lindhardt, Vibeke ; Mc William, Martin ; Patt, Irina ; Sass, Louise ; Vázquez, Miguel ; Verdyk, Marie-José ; Verroken, Andre ; Vogt, Wiebke ; von Harten, Beate ; Waugh, Tatheen ; Wittocx, Herman ; Zellweger, Christoph ; Zib, Nils-Ole
boek